Alterações estruturais e comunicação intercelular no periodonto submetido à oclusão traumática - Debortoli, Caio Vinícius Lourenço [UNESP] (2015)
Primary occlusal trauma has been defined as an injury to the attachment apparatus as a result of excessive occlusal force applied to a tooth or teeth with normal and healthy support tissues. This study aims were to evaluate the structural and histochemical changes of the periodontal ligament and bone around the roots; submitted to traumatic occlusion. For this study, 80 Wistar rats of seven weeks old were divided into Control (C) and Traumatic Occlusion (TO) group, in a period of study of 2, 5, 7 and 14 days. The TO group had the inferior right first molar raised by composite direct filling. The quantitative analyses were done in the sections immunostaining with connexin 43 (Cx43) and runt-related transcription factor 2 (RUNX 2), and histochemically stain with tartrate resistant acid phosphatase (TRAcP); counterstained with hematoxylin and eosin (HE) to verify blood vessel number and area, extracellular matrix area and number of cellular profile; and Masson's to measure collagen fibers area of the periodontal ligament of the distal root of the right lower first molar. The Mann-Whitney U test was used for group comparison. TO group showed on the mesial side of the root a decreased percentage of collagen fiber area (5 and 7 days; p value respectivly 0.03 and 0.05) and an increase in the periodontal ligament width (day 2, p=0.05); and on the distal side of the root show a decrease in the blood vessels area (day 2, p=0.03), increase in the number of nuclear profiles (day 2, p=0.03 and day 7, p=0.05). The increase in the area of fibrillar cellular matrix occurs in both side of the root. The number of immuno reactive cells for Cx43 (Day 5 and 7; p = 0.03) TRAcP (Day 2 and 7; p=0.029 and 0.016 respectively) and RUNX 2 (Day 5, p=0.03) increased in the distal side. The changes observed in the periodontium in front of traumatic occlusion are related...